Looking into the mirror: the Bible, normativity and reflexivity - Rogers, Andrew (Practical theology, 2023)
British and Irish practical theology has been exercised in its recent history about the apparent elusiveness of the Bible within practical theology. In this essay, I want to address how we might now move beyond the pathology of Bible and practical theology, to thinking about the ways in which the Bible may function normatively in practical theology. This was prompted by teaching reflexivity in a professional doctorate programme and noting the almost complete absence of the Bible from the literature on this topic. How is it that a book of mirrors and examinations, vigilance and virtue, powers and unveilings has been excluded from our reflexivity curriculum? As a case study of the Bible’s normativity, and inspired by using M. C. Escher mirrors in the classroom, this essay looks into five biblical mirrors to engage in a practical theological reading of Scripture that speaks to reflexivity and its conundrums. Through a variety of normative moves, I argue that the mirrors offer epistemological and ontological insights that show reflexivity to be a practice with its own theological integrity. This theological reflexivity is then worked out in a number of actions for the classroom and beyond.